Competence potential of new textbooks on geography according to National Academy of Sciences - Рудик, О. О. (Київський національний університет імені Тараса Шевченка, 2024)
The article examines modern geography textbooks for grades 6-7 and their compliance with the competency-based requirements of the New Ukrainian School. It analyzes the contribution of these textbooks to the development of key competencies, such as research, environmental, and social-communicative skills. The role of textbooks in fostering practical skills, critical thinking, and creativity among students is discussed in detail. Special attention is given to the integration of digital technologies, visual aids, and interdisciplinary approaches into the learning process. The importance of updating textbook content to ensure high-quality education aimed at developing active citizenship, awareness of global challenges, and a sustainable ecological mindset is emphasized. Additionally, the article highlights the significance of textbooks in maintaining student motivation through the implementation of interactive tasks and project-based learning methods. The need for adapting educational materials to the age-specific characteristics of students to simplify the understanding of complex geographical concepts is underlined. Examples of successful implementation of competency-based approaches in textbooks are provided, demonstrating how they enable students to apply their knowledge in real-world situations. The paper further discusses the necessity of employing modern teaching methods that prioritize inclusivity, personalization, and active student engagement. It advocates for the development of educational resources that not only meet academic standards but also prepare students for lifelong learning, global awareness, and effective problem-solving. Finally, the article emphasizes the need for ongoing collaboration between educators, researchers, and curriculum developers to create textbooks that reflect current scientific advancements and societal needs.

У статті досліджено сучасні підручники з географії для 6-7 класів, їхню відповідність компетентнісним вимогам Нової української школи. Проаналізовано внесок підручників у розвиток ключових компетентностей, таких як науково-дослідницька, екологічна, соціально-комунікативна. Розглянуто роль підручників у формуванні практичних навичок, критичного мислення та творчих здібностей учнів. Особливу увагу приділено інтеграції цифрових технологій, візуальних засобів і міждисциплінарних підходів у навчальний процес. Наголошено на важливості оновлення змісту підручників для забезпечення якісної освіти, спрямованої на розвиток активної громадянської позиції, усвідомлення глобальних викликів сучасності та формування стійкого екологічного світогляду. Окремо висвітлено значення підручників у підтримці мотивації учнів до навчання через впровадження інтерактивних завдань та проєктних методів. Акцентовано на важливості адаптації навчального матеріалу до вікових особливостей школярів для полегшення сприйняття складних географічних понять. Зроблено висновки про необхідність використання сучасних методик викладання.
Компетентнісний потенціал нових підручників з географії за НУШ
Keywords: компетентність; географічна освіта; НУШ; підручник з географії; компететнісний підхід; competence; geographical education; geography textbook; competence approach